2016
DOI: 10.18632/oncotarget.7133
|View full text |Cite
|
Sign up to set email alerts
|

Exo70 is transcriptionally up-regulated by hepatic nuclear factor 4α and contributes to cell cycle control in hepatoma cells

Abstract: Exo70, a member of the exocyst complex, is involved in cell exocytosis, migration, invasion and autophagy. However, the expression regulation and function of Exo70 in hepatocellular carcinoma are still poorly understood. In this study, we found Exo70 expression in human hepatoma cells was greatly reduced after knocking down hepatic nuclear factor 4α (HNF4α), the most important and abundant transcription factor in liver. This regulation occurred at the transcriptional level but not post-translational level. HNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Knockdown of Exo70 in MDA-MB-231 cells abolished the secretion of MMPs, whereas the overexpression of Exo70 promoted MMP secretion 22 . From HeLa cells and MDA-MB-231 cells, Exo70 directly interacts with the Arp2/3 complex, a core nucleating factor for the generation of branched actin networks for cell morphogenesis and migration 21 . And this interaction is important for the regulation of actin assembly at the leading edge of migrating cells 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Exo70 in MDA-MB-231 cells abolished the secretion of MMPs, whereas the overexpression of Exo70 promoted MMP secretion 22 . From HeLa cells and MDA-MB-231 cells, Exo70 directly interacts with the Arp2/3 complex, a core nucleating factor for the generation of branched actin networks for cell morphogenesis and migration 21 . And this interaction is important for the regulation of actin assembly at the leading edge of migrating cells 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Exo70 is also reported to accelerate polarized lysosome secretion at the immune synapse and promote cell migration and invasion in multiple types of tumors [22][23][24][25][26]. In previous studies, we reported that Exo70 affects the progression of liver cancer and breast cancer [27,28]. However, it remains to be seen whether Exo70 is involved in the tumorigenesis, progression, or platinum resistance of EOC.…”
Section: Introductionmentioning
confidence: 90%
“…Pyroptosis is a programmed cell death based on caspase-1. 99,100 According to an investigation, BBR (20 μg/ml) induced cell cycle arrest in the G0/G1 phase in T-ALL Jurkat cells. 101 It was also revealed that BBR induced G1 arrest and apoptosis by increasing p27Kip1 and decreasing Cyclin D, Cyclin E, CDK2, and CDK4 in glioblastoma cells.…”
Section: Bbr and Cell Cycle Arrestmentioning
confidence: 99%